FRI0116 Impact of prior biologic use on treatment response in patients with rheumatoid arthritis receiving adalimumab in routine clinical care: results from the passion study. (12th June 2018) - Van den Bosch, F.; Wassenberg, S.; Zueger, P.; Kalabic, J.; Wu, M.; Monastiriakos, K.; Ostor, A.
Abstract : Background: It is recognised that early diagnosis and treatment are important in maximising long-term quality of life in patients (pts) with rheumatoid arthritis (RA). Prior biologic disease modifying antirheumatic drug (bDMARD) use has been shown to affect treatment response to further biologic therapy including adalimumab (ADA). Objectives: To evaluate the impact of prior bDMARD use on clinical and pt-reported outcomes in pts enrolled in the PASSION study. Methods: PASSION was a 78-wk postmarketing, multinational, observational study that assessed the effectiveness of ADA in pts with moderate to severe RA receiving ADA in routine clinical care in the context of participation in the voluntary AbbVie pt support program. Pts with an insufficient response to ≥1 DMARD (1 prior bDMARD was allowed) and newly initiating ADA were enrolled and categorised as bDMARD-naïve or bDMARD-experienced. For the present analysis, ADA treatment response was determined by evaluating least squares (LS) mean change from baseline for multiple clinical and pt-reported outcomes (table 1). Missing data for each efficacy endpoint were imputed using last observation carried forward, and differences between groups for efficacy endpoints at wks 24, 52, and 78 were based on ANCOVA models adjusting for baseline and demographic variables (table 1). Additionally, the percentages of pts at each time point (observed population) who achieved HAQ-DI minimal clinically important difference (MCID; improvement from baseline of ≥0.22) were assessed. Results: Of 1025 pts included in the intent-to-treat population, 182 were bDMARD-experienced and 843 were bDMARD-naïve at baseline. There were no significant differences between groups in sex, race, ethnicity, weight, height, body mass index, TJC28, SJC28, and pain at baseline. However, bDMARD-experienced pts were significantly older, had longer RA duration, and had lower values for HAQ-DI, DAS28(CRP), CDAI, SDAI, PtGA, and PhGA than bDMARD-naïve pts at baseline (p<0.05 for all). ADA treatment response was significantly higher for bDMARD-naïve vs bDMARD-experienced pts at all timepoints for HAQ-DI, DAS28(CRP), CDAI, PtGA, and pain, at wks 24 and 52 for SDAI, and at wk 24 for TJC28 and SJC28 (table 1). In the observed population, a large percentage of bDMARD-naïve and bDMARD-experienced pts achieved HAQ-DI MCID at wk 24 (67% and 60%), wk 52 (71% and 65%), and wk 78 (74% and 59%). Conclusions: Among pts with moderate to severe RA that initiated ADA treatment in the PASSION study, bDMARD-naïve pts achieved significantly larger improvements from baseline to wk 78 in a variety of clinical and pt-reported outcomes compared with bDMARD-experienced pts. A large proportion of both bDMARD-naïve and bDMARD-experienced pts achieved HAQ–DI MCID with ADA treatment. Acknowledgements: AbbVie funded the study and analysis, and approved the abstract for submission. Medical writing support was provided by Wendy van der Spuy, PhD, of Complete Healthcare Communications, LLC (West Chester, PA, USA), and was funded by AbbVie. Disclosure of Interest: F. Van den Bosch Grant/research support from: AbbVie, Bristol-Myers Squibb, Celgene, Janssen, Lilly, Merck, Novartis, Pfizer, and UCB, Consultant for: AbbVie, Bristol-Myers Squibb, Celgene, Janssen, Lilly, Merck, Novartis, Pfizer, and UCB, Speakers bureau: AbbVie, Bristol-Myers Squibb, Celgene, Janssen, Lilly, Merck, Novartis, Pfizer, and UCB, S. Wassenberg Grant/research support from: AbbVie, BMS, Fuji, Gilead, Novartis, Pfizer, Roche, Sandoz, and UCB, Consultant for: AbbVie, Celgene, Janssen, Chugai, Lilly, Novartis, Pfizer, MSD, and UCB, Speakers bureau: AbbVie, Celgene, Janssen, Chugai, Lilly, Novartis, Pfizer, MSD, and UCB, P. Zueger Employee of: AbbVie, J. Kalabic Employee of: AbbVie, M. Wu Employee of: AbbVie, K. Monastiriakos Employee of: AbbVie, A. Ostor Grant/research support from: Lilly, Roche, MSD, AbbVie, Pfizer, Novartis, Janssen, and Bristol-Myers Squibb, Consultant for: Lilly, Roche, MSD, AbbVie, Pfizer, Novartis, Janssen, and Bristol-Myers Squibb